Balance of the 7th Scenic Meeting (The Voz a Vos Bulletin, 2021)
Summary of the schedule and guests of the 7th Scenic Meeting: Manuel Zapata Olivella - Tradition and Identity that took place from September 17 to 19, 2020 with success in a digital edition.
Keywords: Zapata; Scenic meeting; Tradition